INTEGRATING CHARACTER EDUCATION INTO SCIENCE LEARNING TO IMPROVE ACADEMIC ACHIEVEMENT AT SMA TELUK DALAM - Harefa, Darmawan (TUNAS : Jurnal Pendidikan Biologi, 2025)
This study aims to examine the impact of character education integration in science learning on improving students' academic achievement at SMA Negeri 1 Teluk Dalam. Character values such as honesty, responsibility, cooperation, and curiosity were embedded into every stage of the science learning process to foster positive attitudes and enhance scientific concept mastery. A qualitative research approach with a case study design was employed, using observation, interviews, and documentation for data collection. The findings indicate that consistent implementation of character education strategies significantly improves students’ learning motivation, active engagement, and academic performance in science subjects. These results highlight the crucial role of teachers in selecting appropriate instructional models and designing lesson plans (RPP) that incorporate character education indicators. Furthermore, the study underscores the necessity of a supportive school environment to optimize the holistic implementation of character education. Thus, integrating character education into science learning not only enhances academic achievement but also nurtures a generation with strong character, prepared to face future challenges.